893 Development of a Rabbit Human Glioblastoma Model for Testing of Endovascular Selective Intra-Arterial Infusion (ESIA) of Novel Stem Cell-Based Therapeutics. (April 2023) - Srinivasan, Visish M.; Kan, Peter; Gumin, Joy; Collins, Dalis E.; Chen, Stephen; Chen, Melissa M.; Garcia, Robert; Fueyo, Juan; Lang, Frederick F.
Abstract : INTRODUCTION: Poor outcomes for glioblastoma (GBM) are partly due to the inability to deliver therapeutic agents to the tumor because of the blood brain barrier (BBB) as well as ineffective agents. We have evaluated bone marrow-derived mesenchymal stem cells (MSCs) as transport vehicles of biological therapeutics, particularly Delta-24-RGD (D24), an engineered tumor-selective oncolytic adenovirus that replicates and lyses only in human tumor cells. In mice, we have shown that MSCs loaded with D24 (MSCs-D24) home to GBMs after intra-arterial (IA) carotid infusion, resulting in widespread distribution in the tumor and oncolysis. Intravenous infusion is ineffective, rendering IA delivery the only effective systemic option. To understand the applicability of IA infusions of MSCs-D24 requires a large animal, human brain tumor model recapitulating the challenges of clinical use. METHODS: Rabbits underwent stereotactic xenoimplantation of human GBM cell lines. Tumor creation was confirmed on magnetic resonance imaging (MRI), histologic and immunohistochemistry analysis. Selective internal carotid artery MSCs-D24 infusion ipsilateral to the tumor was performed assess efficacy and safety. RESULTS: We report on successful xenoimplantation of human glioblastoma cell lines (U87, GSC17, and GSC8-11) in 28 immunosuppressed rabbits using Mycophenolate Mofetil, Dexamethasone, and Tacrolimus. The implanted rabbits were followed for 35 days prior to tumor assessment with MRI, angiography, and histological analysis. On MRI, the tumors were hyperintense on T2-weighted image and enhanced (evidence of BBB breakdown). On histological analysis, tumors showed phenotypic traits of human GBM and display varying levels of vascularity, an important feature for testing IA therapy. Selective internal carotid artery MSCs-D24 infusion was safe in the model, and MSCs-D24 homed to the implanted tumor at 24 hours. CONCLUSIONS: The intracranial immunosuppressed rabbit human GBM model allows testing of ESIA infusion of novel therapeutics (eg. MSCs-D24) in a clinically relevant fashion.